1998
DOI: 10.1046/j.1365-2680.1998.1820099.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous adenosine and its monophosphate on the contractile response to acetylcholine in the human isolated detrusor muscle strips

Abstract: 1. Adenosine (0.1-1 mM) or its 5'-monophosphate (5'-AMP) induced a concentration-dependent relaxation of tension caused by acetylcholine (0.2 microM) in human urinary bladder detrusor strips. 2. This effect was antagonized concentration dependently by theophylline at an apparent pA2 value of about 5. 3. Maximum relaxation by adenosine or 5'-AMP never exceeded 50% and 80%, respectively, of acetylcholine-induced tension. Relaxation by some beta2-adrenoceptor agonists (0.1-0.2 mM) or norepinephrine was limited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…Several authors have shown that adenosine directly relaxes pre-contracted urinary bladder detrusor strips in different species [10][11][12][13][14], including humans [15]. However, our results clearly indicate that adenosine-induced relaxation of detrusor contractions requires high (unphysiological) millimolar concentrations of the nucleoside.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Several authors have shown that adenosine directly relaxes pre-contracted urinary bladder detrusor strips in different species [10][11][12][13][14], including humans [15]. However, our results clearly indicate that adenosine-induced relaxation of detrusor contractions requires high (unphysiological) millimolar concentrations of the nucleoside.…”
Section: Discussioncontrasting
confidence: 51%
“…Despite the observation that adenosine is able to relax precontracted detrusor strips from the human bladder [15], we found that this is only valid for concentrations of the nucleoside in the millimolar range (Fig. 4).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Adenosine directly relaxes precontracted urinary bladder detrusor strips in different species (1,8,9,33,43), including humans (51). Notwithstanding this, we recently showed that adenosine-induced relaxation of detrusor contractions requires high (millimolar) concentrations of the nucleoside compared with those required to decrease nerve-evoked ACh release from human detrusor strips (54).…”
mentioning
confidence: 99%
“…Adenosine is a breakdown product of ATP via endonucleotidases, and stimulates different types of the P1 class of adenosine receptors (A 1 , A 2A , A 2B , and A 3 ). In the human bladder, adenosine relaxes contractions induced by agonists, and electrical stimulation of nerves . and reduces stretch‐activated urothelial ATP release .…”
Section: Methodsmentioning
confidence: 99%